A method for recovering precious metals from waste
By using an adsorbent made of flake graphite and carboxymethyl cellulose, combined with dithio amino groups, the complex and cost-effective precious metal recycling in the prior art is solved, and efficient precious metal recycling is achieved. Especially the high recovery rate of gold and platinum.
Patent Information
- Application Number
- CN202410537955.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-04-26
AI Technical Summary
The prior art methods for recycling precious metals from waste liquids are complex and costly, making it difficult to achieve high recovery rates.
Using composite adsorbents, made of flake graphite and carboxymethyl cellulose as substrates, the adsorbents with a three-dimensional network structure are formed by amino modification and chemical grafting. The adsorbents are combined with dithio amino groups for adsorption and recovery. Precious metals in waste liquid.
The recycling process is simplified, the recovery rate of precious metals is improved, especially the recycling efficiency of gold and platinum, and efficient precious metal recycling is achieved.
Smart Images

Figure CN118531220B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of precious metal recovery, and in particular to a method for recovering precious metals from waste. Background Art
[0002] Precious metals mainly refer to eight metal elements, including gold, silver and platinum group metals (ruthenium, rhodium, palladium, osmium, iridium, platinum). These metals are rare in nature and difficult to mine, so they are expensive. They have a series of unique physical and chemical properties, such as optical properties, density, thermal conductivity, electrical conductivity, melting point and boiling point, which make precious metals widely used in many fields: for example, microprobes made of precious metals can be used to explore the nervous system and repair damaged parts, such as visual nerve repair devices; precious metal isotopes and compounds can also be used for the diagnosis and treatment of diseases and tumors such as liver, lung, kidney, breast, brain, etc.; in the field of aerospace, precious metals also play an indispensable role. The aviation, aerospace and marine industries have extremely high requirements for materials, requiring materials to have high temperature corrosion resistance, high reliability, high precision and long service life, and precious metals just meet these requirements; in addition, precious metals are also widely used in information technology and laser technology. With the development of electronic computers, information technology has been greatly promoted, and precious metals have played an important role in it.
[0003] Since precious metals are rare and expensive materials, it is required to recycle the precious metals contained in waste as much as possible and reuse them. Precious metal waste liquid is an important part of precious metal secondary resources. Recycling precious metals in these waste liquids can not only improve economic benefits and solve the problem of precious metal resource scarcity in my country, but also help protect the environment. Therefore, studying new methods and processes for recovering precious metals from waste liquids will have important theoretical and practical significance.
[0004] Chinese patent document CN202010894353.6 discloses a method for recovering precious metals from strongly acidic waste liquid, which uses a metal ion adsorbent to perform staged chelation sedimentation treatment on the filtrate of the strongly acidic waste liquid, and the chelation pH values in different stages are 1-3, 3-5 and 5-7, respectively. Different complexing agents are used for coordinated sedimentation treatment in different stages, and the precipitate is collected and then subjected to high-temperature ashing, and the ashing components are collected, dissolved and removed with acid, and then reduced to obtain a mixture with a high content of precious metals. The method disclosed in the patent has a long recovery process, a complex treatment process, and a high cost. Summary of the invention
[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for recovering precious metals from waste, which method has the characteristics of simple operation and high recovery rate of precious metals.
[0006] In order to achieve the above object, the present invention adopts the following technical scheme:
[0007] A method for recovering precious metals from waste, comprising the following steps:
[0008] S1, preliminarily filtering the waste liquid to obtain a filtrate;
[0009] S2, adjusting the pH of the filtrate obtained in step S1 to 5-7, then adding the composite adsorbent thereto, stirring and adsorbing at room temperature for 3-5 hours, after the adsorption is completed, filtering and collecting the filter residue, washing the filter residue to neutrality, and drying;
[0010] S3, ashing the filter residue dried in step S2, grinding it, washing it with dilute hydrochloric acid, and filtering it to obtain a solid product;
[0011] S4, calcining the solid product in step S3 under a hydrogen atmosphere to obtain a noble metal mixture;
[0012] Wherein, in step S2, the preparation method of the composite adsorbent is as follows:
[0013] (1) adding oxidized carboxymethyl cellulose and polyethyleneimine to PBS buffer, stirring evenly, then adding activators EDC and NHS, stirring for 12-24 hours, and dialysis purification to obtain amino-modified cellulose;
[0014] (2) ultrasonically dispersing graphite flakes in an ethanol aqueous solution, then adding an aminosilane coupling agent thereto, stirring for 2-5 hours, and then filtering, washing, and drying to obtain amino-modified graphite flakes;
[0015] (3) The amino-modified cellulose and the amino-modified flake graphite are ultrasonically dispersed in deionized water, and then glutaraldehyde is added thereto to adjust the pH of the solution to 9-12, and the reaction is heated and stirred. After the reaction is completed, the mixture is cooled to room temperature, and then carbon disulfide is added thereto to adjust the pH of the solution to 9-12, and stirring is continued for 2-4 hours. After filtering, washing, and drying, a composite adsorbent is obtained.
[0016] Specifically, in step (1), the preparation method of the oxidized carboxymethyl cellulose is as follows: carboxymethyl cellulose is added to deionized water, stirred evenly, then 3-5 times the mass of sodium hypochlorite is added, stirred evenly, reacted in the dark for 2-3 hours, then ethylene glycol is added to terminate the reaction, and the oxidized carboxymethyl cellulose is obtained by dialysis, concentration, and freeze-drying.
[0017] Specifically, the mass ratio of oxidized carboxymethyl cellulose, polyethyleneimine, EDC and NHS is 10-15:6-10:3-5:2-4. In some embodiments of the present invention, for example, 10:6:3:2, 10:8:4:3, 10:10:5:4, 12:8:4:3, 15:6:3:2, 15:8:4:3, 15:10:4:3, 15:10:5:4 can be selected, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] Specifically, in step (1), the concentration of the selected PBS buffer is 0.2 mol / L and the pH is 7.4.
[0019] Specifically, in step (2), the mass ratio of flake graphite to aminosilane coupling agent is 8-12:1-3. In some embodiments of the present invention, for example, 8:1, 8:2, 8:3, 10:1, 10:3, 12:1, 12:2, 12:3 can be selected, but it is not limited to the listed values. Other values not listed within the numerical range are also applicable.
[0020] Specifically, in step (2), the aminosilane coupling agent is selected from at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltriisopropoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane and N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane.
[0021] Specifically, in step (3), the mass ratio of amino-modified cellulose, amino-modified flake graphite, glutaraldehyde and carbon disulfide is 10-15:10-15:6-10:4-8. In some embodiments of the present invention, for example, 10:10:6:4, 10:12:8:6, 10:15:10:8, 15:10:6:4, 15:12:8:6, 15:15:6:4, 15:15:10:8 can be selected, but it is not limited to the listed values. Other values not listed within the numerical range are also applicable.
[0022] Specifically, in step (3), the temperature of the heating and stirring reaction is 60-80°C. In some embodiments of the present invention, for example, 60°C, 65°C, 70°C, 75°C, or 80°C can be selected; the time of the heating and stirring reaction is 3-5h. In some embodiments of the present invention, for example, 3h, 4h, or 5h can be selected; but the present invention is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0023] Specifically, in step S2, the addition amount of the composite adsorbent is 5-10 g / L. In some embodiments of the present invention, for example, 5 g / L, 6 g / L, 7 g / L, 8 g / L, 9 g / L, and 10 g / L can be selected, but are not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0024] Specifically, in step S3, the ashing temperature is 650-800°C. In some embodiments of the present invention, for example, 650°C, 680°C, 700°C, 720°C, 750°C, and 800°C can be selected; the ashing time is 1-3h, for example, 1h, 2h, and 3h can be selected, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] Specifically, in step S3, the calcination temperature is 350-450°C. In some embodiments of the present invention, for example, 350°C, 380°C, 400°C, 420°C, and 450°C can be selected; the calcination time is 0.5-2h, for example, 0.5h, 1h, 1.5h, and 2h can be selected; but it is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The composite adsorbent used in the present invention uses flake graphite and carboxymethyl cellulose as substrates. The inorganic material flake graphite in the composite adsorbent has a large specific surface area and has good adsorption performance for precious metals. The organic material carboxymethyl cellulose in the composite adsorbent is a hydrophilic organic polymer that can improve the dispersion performance of the composite adsorbent in water and avoid agglomeration. The present invention improves the adsorption performance of the composite adsorbent for precious metals in waste liquid by combining organic materials with inorganic materials.
[0028] (2) The present invention performs an amino modification treatment on carboxymethyl cellulose and also performs an amino modification treatment on flake graphite. Then, under the action of a cross-linking agent, glutaraldehyde, the amino-modified cellulose and the amino-modified flake graphite are chemically grafted to obtain an adsorbent with a three-dimensional network structure. Subsequently, in an alkaline environment, the amino group and carbon disulfide react to obtain a dithioamino group with a stronger adsorption capacity for precious metals. Finally, under the synergistic effect of the dithioamino group and the adsorption substrate, the recovery rate of precious metals such as gold and platinum is effectively improved.
[0029] (3) The present invention performs ashing, impurity dissolution and reduction treatment on the filter residue adsorbed with precious metals, thereby obtaining a mixture containing precious metals and achieving preliminary recovery of precious metals. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1It is a rendering of the precious metal recovery rate of Examples 1-3 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.
[0032] It should be noted that, unless otherwise specified, the chemical reagents involved in the present invention were purchased through commercial channels.
[0033] The mesh number of the flake graphite powder used in the present invention is 400 meshes; the relative molecular mass of polyethyleneimine is 3000.
[0034] Example 1
[0035] A method for recovering precious metals from waste, comprising the following steps:
[0036] S1, preliminarily filtering the waste liquid to obtain a filtrate;
[0037] S2, adjusting the pH of the filtrate obtained in step S1 to 6.0, then adding 10 g of the composite adsorbent to 1 L of the filtrate, stirring and adsorbing at room temperature for 4 h, after the adsorption is completed, filtering to obtain a filter residue and a test solution, washing the filter residue to neutrality, and drying;
[0038] The preparation method of the composite adsorbent is as follows:
[0039] (1) adding 10 g of carboxymethyl cellulose to 100 mL of deionized water, stirring evenly, then adding 30 g of sodium hypochlorite, stirring evenly, reacting in the dark for 2 h, then adding ethylene glycol to terminate the reaction, dialyzing, concentrating, and freeze-drying to obtain oxidized carboxymethyl cellulose;
[0040] (2) 10 g of oxidized carboxymethyl cellulose and 6 g of polyethyleneimine were added to 100 mL of PBS buffer and stirred evenly, and then 3 g of activator EDC and 2 g of NHS were added, stirred for 16 h, and dialyzed for purification to obtain amino-modified cellulose;
[0041] (3) 10 g of flake graphite was ultrasonically dispersed in 100 mL of 75 wt% ethanol aqueous solution, and then 1 g of 3-aminopropyltrimethoxysilane was added thereto, stirred for 3 h, and then filtered, washed, and dried to obtain amino-modified flake graphite;
[0042] (4) 10 g of amino-modified cellulose and 10 g of amino-modified flake graphite were ultrasonically dispersed in 150 mL of deionized water, and then 6 g of glutaraldehyde was added thereto, and the pH of the solution was adjusted to 10. The mixture was heated and stirred at 60 °C for 5 h. After the reaction was completed, the mixture was cooled to room temperature, and then 4 g of carbon disulfide was added thereto, and the pH of the solution was adjusted to 12. The mixture was stirred for 2 h. After filtering, washing, and drying, a composite adsorbent was obtained.
[0043] S3, ashing the dried residue in step S2 at 700° C. for 2 h, grinding it, washing it with dilute hydrochloric acid, and filtering it to obtain a solid product;
[0044] S4, calcining the solid product in step S3 under a hydrogen atmosphere at a calcination temperature of 400° C. for 1 h to obtain a noble metal mixture.
[0045] Example 2
[0046] A method for recovering precious metals from waste, comprising the following steps:
[0047] S1, preliminarily filtering the waste liquid to obtain a filtrate;
[0048] S2, adjusting the pH of the filtrate obtained in step S1 to 6.0, then adding 5g of the composite adsorbent to 1L of the filtrate, stirring and adsorbing at room temperature for 3h, after the adsorption is completed, filtering to obtain a filter residue and a test solution, washing the filter residue to neutrality, and drying;
[0049] The preparation method of the composite adsorbent is as follows:
[0050] (1) adding 10 g of carboxymethyl cellulose to 100 mL of deionized water, stirring evenly, then adding 50 g of sodium hypochlorite, stirring evenly, reacting in the dark for 2 h, then adding ethylene glycol to terminate the reaction, dialyzing, concentrating, and freeze-drying to obtain oxidized carboxymethyl cellulose;
[0051] (2) 15 g of oxidized carboxymethyl cellulose and 10 g of polyethyleneimine were added to 100 mL of PBS buffer and stirred evenly. Then, 5 g of activator EDC and 4 g of NHS were added, stirred for reaction for 24 h, and dialyzed for purification to obtain amino-modified cellulose;
[0052] (3) 8 g of flake graphite was ultrasonically dispersed in 100 mL of 75 wt% ethanol aqueous solution, and then 1 g of 3-aminopropyltriethoxysilane was added thereto, stirred for 5 h, and then filtered, washed, and dried to obtain amino-modified flake graphite;
[0053] (4) 10 g of amino-modified cellulose and 15 g of amino-modified flake graphite were ultrasonically dispersed in 150 mL of deionized water, and then 8 g of glutaraldehyde was added thereto, and the pH of the solution was adjusted to 10. The mixture was heated and stirred at 60 °C for 5 h. After the reaction was completed, the mixture was cooled to room temperature, and then 6 g of carbon disulfide was added thereto, and the pH of the solution was adjusted to 12. The mixture was stirred for 2 h. After filtering, washing, and drying, a composite adsorbent was obtained.
[0054] S3, ashing the dried residue in step S2 at 700° C. for 2 h, grinding it, washing it with dilute hydrochloric acid, and filtering it to obtain a solid product;
[0055] S4, calcining the solid product in step S3 under a hydrogen atmosphere at a calcination temperature of 400° C. for 1 h to obtain a noble metal mixture.
[0056] Example 3
[0057] A method for recovering precious metals from waste, comprising the following steps:
[0058] S1, preliminarily filtering the waste liquid to obtain a filtrate;
[0059] S2, adjusting the pH of the filtrate obtained in step S1 to 6.0, then adding 8 g of the composite adsorbent to 1 L of the filtrate, stirring and adsorbing at room temperature for 3 h, after the adsorption is completed, filtering to obtain a filter residue and a test solution, washing the filter residue to neutrality, and drying;
[0060] The preparation method of the composite adsorbent is as follows:
[0061] (1) adding 10 g of carboxymethyl cellulose to 100 mL of deionized water, stirring evenly, then adding 40 g of sodium hypochlorite, stirring evenly, reacting in the dark for 2 h, then adding ethylene glycol to terminate the reaction, dialyzing, concentrating, and freeze-drying to obtain oxidized carboxymethyl cellulose;
[0062] (2) 12 g of oxidized carboxymethyl cellulose and 8 g of polyethyleneimine were added to 100 mL of PBS buffer and stirred evenly, and then 4 g of activator EDC and 3 g of NHS were added, stirred for 12 h, and dialyzed for purification to obtain amino-modified cellulose;
[0063] (3) 12 g of flake graphite was ultrasonically dispersed in 100 mL of 75 wt% ethanol aqueous solution, and then 3 g of 3-aminopropyltriethoxysilane was added thereto, stirred for 2 h, and then filtered, washed, and dried to obtain amino-modified flake graphite;
[0064] (4) 15 g of amino-modified cellulose and 12 g of amino-modified flake graphite were ultrasonically dispersed in 150 mL of deionized water, and then 10 g of glutaraldehyde was added thereto, and the pH of the solution was adjusted to 10. The mixture was heated and stirred at 60 °C for 5 h. After the reaction was completed, the mixture was cooled to room temperature, and then 8 g of carbon disulfide was added thereto, and the pH of the solution was adjusted to 12. The mixture was stirred for 2 h. After filtering, washing, and drying, a composite adsorbent was obtained.
[0065] S3, ashing the dried residue in step S2 at 700° C. for 2 h, grinding it, washing it with dilute hydrochloric acid, and filtering it to obtain a solid product;
[0066] S4, calcining the solid product in step S3 under a hydrogen atmosphere at a calcination temperature of 450° C. for a calcination time of 0.5 h to obtain a noble metal mixture.
[0067] Comparative Example 1
[0068] A method for recovering precious metals from waste, comprising the following steps:
[0069] S1, preliminarily filtering the waste liquid to obtain a filtrate;
[0070] S2, adjusting the pH of the filtrate obtained in step S1 to 6.0, then adding 8 g of adsorbent to 1 L of the filtrate, stirring and adsorbing at room temperature for 3 h, after the adsorption is completed, filtering to obtain a filter residue and a test solution, washing the filter residue to neutrality, and drying;
[0071] The preparation method of the adsorbent is as follows:
[0072] (1) 12 g of flake graphite was ultrasonically dispersed in 100 mL of 75 wt% ethanol aqueous solution, and then 3 g of 3-aminopropyltriethoxysilane was added thereto, stirred for 2 h, and then filtered, washed, and dried to obtain amino-modified flake graphite;
[0073] (2) 12 g of amino-modified flake graphite was ultrasonically dispersed in 150 mL of deionized water, and the pH of the solution was adjusted to 10. Then, 8 g of carbon disulfide was added thereto, and the mixture was stirred at room temperature for 2 h. After filtering, washing, and drying, an adsorbent was obtained.
[0074] S3, ashing the dried residue in step S2 at 700° C. for 2 h, grinding it, washing it with dilute hydrochloric acid, and filtering it to obtain a solid product;
[0075] S4, calcining the solid product in step S3 under a hydrogen atmosphere at a calcination temperature of 450° C. for a calcination time of 0.5 h to obtain a noble metal mixture.
[0076] Comparative Example 2
[0077] A method for recovering precious metals from waste, comprising the following steps:
[0078] S1, preliminarily filtering the waste liquid to obtain a filtrate;
[0079] S2, adjusting the pH of the filtrate obtained in step S1 to 6.0, then adding 8 g of the composite adsorbent to 1 L of the filtrate, stirring and adsorbing at room temperature for 3 h, after the adsorption is completed, filtering to obtain a filter residue and a test solution, washing the filter residue to neutrality, and drying;
[0080] The preparation method of the composite adsorbent is as follows:
[0081] (1) adding 10 g of carboxymethyl cellulose to 100 mL of deionized water, stirring evenly, then adding 40 g of sodium hypochlorite, stirring evenly, reacting in the dark for 2 h, then adding ethylene glycol to terminate the reaction, dialyzing, concentrating, and freeze-drying to obtain oxidized carboxymethyl cellulose;
[0082] (2) 12 g of oxidized carboxymethyl cellulose and 8 g of polyethyleneimine were added to 100 mL of PBS buffer and stirred evenly, and then 4 g of activator EDC and 3 g of NHS were added, stirred for 12 h, and dialyzed for purification to obtain amino-modified cellulose;
[0083] (3) 12 g of flake graphite was ultrasonically dispersed in 100 mL of 75 wt% ethanol aqueous solution, and then 3 g of 3-aminopropyltriethoxysilane was added thereto, stirred for 2 h, and then filtered, washed, and dried to obtain amino-modified flake graphite;
[0084] (4) 15 g of amino-modified cellulose and 12 g of amino-modified flake graphite were ultrasonically dispersed in 150 mL of deionized water, and then 10 g of glutaraldehyde was added thereto. The pH of the solution was adjusted to 10, and the solution was heated and stirred at 60 ° C for 5 h. After the reaction was completed, the composite adsorbent was obtained by filtering, washing and drying.
[0085] S3, ashing the dried residue in step S2 at 700° C. for 2 h, grinding it, washing it with dilute hydrochloric acid, and filtering it to obtain a solid product;
[0086] S4, calcining the solid product in step S3 under a hydrogen atmosphere at a calcination temperature of 450° C. for a calcination time of 0.5 h to obtain a noble metal mixture.
[0087] After the waste liquid in the embodiment of the present invention was filtered, the concentration of Au(III) was detected to be 8.37 mg / L, and the concentration of Pd(II) was detected to be 11.84 mg / L.
[0088] Then, the concentrations of Au(III) and Pd(II) were tested for the test solution in step S2 of Example 1-3 and Comparative Example 1-2, and the recovery rate of each noble metal ion was calculated. The test results are as follows: Figure 1 As shown, from Figure 1 It can be seen that the recovery rate of Au(III) in the embodiments of the present invention is more than 99%, and the recovery rate of Pd(II) is more than 98%. Compared with Example 3, Comparative Example 1 uses a single flake graphite as the matrix, and Comparative Example 2 does not introduce dithioamino groups compared to Example 3. The recovery rates of Au(III) and Pd(II) in Comparative Examples 1-2 are significantly reduced.
[0089] Finally, it should be noted that the above embodiments do not limit the present invention in any form. For those skilled in the art, some modifications and improvements can be made to the present invention. Therefore, any modifications or improvements made without departing from the spirit of the present invention are within the scope of the present invention.
Claims
1. A method for recovering precious metals from waste, characterized in that: The steps include: S1, preliminarily filtering the waste liquid to obtain a filtrate; S2, adjusting the pH of the filtrate obtained in step S1 to 5-7, then adding the composite adsorbent thereto, stirring and adsorbing at room temperature for 3-5 hours, after the adsorption is completed, filtering and collecting the filter residue, washing the filter residue to neutrality, and drying; S3, ashing the filter residue dried in step S2, grinding it, washing it with dilute hydrochloric acid, and filtering it to obtain a solid product; S4, calcining the solid product in step S3 under a hydrogen atmosphere to obtain a noble metal mixture; Wherein, in step S2, the preparation method of the composite adsorbent is as follows: (1) adding oxidized carboxymethyl cellulose and polyethyleneimine to PBS buffer, stirring evenly, then adding activators EDC and NHS, stirring for 12-24 hours, and dialysis purification to obtain amino-modified cellulose; (2) ultrasonically dispersing graphite flakes in an ethanol aqueous solution, then adding an aminosilane coupling agent thereto, stirring for 2-5 hours, and then filtering, washing, and drying to obtain amino-modified graphite flakes; (3) The amino-modified cellulose and the amino-modified flake graphite are ultrasonically dispersed in deionized water, and then glutaraldehyde is added thereto to adjust the pH of the solution to 9-12, and the reaction is heated and stirred. After the reaction is completed, the mixture is cooled to room temperature, and then carbon disulfide is added thereto to adjust the pH of the solution to 9-12, and stirring is continued for 2-4 hours. After filtering, washing, and drying, a composite adsorbent is obtained.
2. The method for recovering precious metals from waste according to claim 1, characterized in that: In step (1), the preparation method of the oxidized carboxymethyl cellulose is as follows: carboxymethyl cellulose is added to deionized water, stirred evenly, then 3-5 times the mass of sodium hypochlorite is added, stirred evenly, reacted in the dark for 2-3 hours, then ethylene glycol is added to terminate the reaction, dialyzed, concentrated, and freeze-dried to obtain oxidized carboxymethyl cellulose.
3. The method for recovering precious metals from waste according to claim 1, characterized in that: In step (1), the mass ratio of oxidized carboxymethyl cellulose, polyethyleneimine, EDC and NHS is 10-15:6-10:3-5:2-4.
4. The method for recovering precious metals from waste according to claim 1, characterized in that: In step (2), the mass ratio of flake graphite to aminosilane coupling agent is 8-12:1-3.
5. The method for recovering precious metals from waste according to claim 1, characterized in that: In step (2), the aminosilane coupling agent is selected from at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyltriisopropoxysilane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane and N-(2-aminoethyl)-3-aminopropylmethyldiethoxysilane.
6. The method for recovering precious metals from waste according to claim 1, characterized in that: In step (3), the mass ratio of amino-modified cellulose, amino-modified flake graphite, glutaraldehyde and carbon disulfide is 10-15:10-15:6-10:4-8.
7. The method for recovering precious metals from waste according to claim 1, characterized in that: In step (3), the temperature of the heating and stirring reaction is 60-80° C., and the time of the heating and stirring reaction is 3-5 h.
8. The method for recovering precious metals from waste according to claim 1, characterized in that: In step S2, the addition amount of the composite adsorbent is 5-10 g / L.
9. The method for recovering precious metals from waste according to claim 1, characterized in that: In step S3, the ashing temperature is 650-800° C., and the ashing time is 1-3 hours.
10. The method for recovering precious metals from waste according to claim 1, characterized in that: In step S3, the calcination temperature is 350-450° C., and the calcination time is 0.5-2 h.
